The Formation of the Anthropological Type of the Uzbek People and the Factors That Influenced This Process (Texas Journal of Philology, Culture and History, 2023)
In this article analyzed how formed antrhroplogical type of Uzbek people. And also it can be shown in this article that more factors impacted to forming of uzbek`s physical appearance and anthropological type